Dukungan Faktor Lingkungan dalam Keberhasilan Rehabilitasi Penyalah Guna Narkotika - Novi Erliyani; Ayun Sriatmi; Mateus Sakundarno Adi (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Rehabilitation of drug abusers is an effort to recover drug abusers from addictive substance dependence, which includes initial reception, medical rehabilitation, and/or social rehabilitation, and post-rehabilitation. Environmental support factors that influence the success of rehabilitation include the economic, social, and political environment. The purpose of this study was to determine the economic, social, and political support in the successful rehabilitation of drug abusers at the National Narcotics Agency Clinic in Central Java Province. This research method is qualitative research with a case study research type. The research uses Van Horn Van Metter analysis with an environmental variable approach. The informants in this study included 8 main informants and 6 triangulation informants. The results of the study stated that economic, social, and political environmental support influenced the successful implementation of sustainable rehabilitation. Client economic support influences the client's willingness to access rehabilitation services. Social support that affects rehabilitation can be from family and the community. Meanwhile, political support both in terms of budget, regulations, and regulations that facilitate the implementation of drug rehabilitation services. The results of this research can be the basis for policy improvement and strengthening environmental support from all stakeholders. Keywords: Policy, Economic, Social, Political, Narcotic.  ABSTRAK Rehabilitasi penyalah guna narkotika merupakan upaya pemulihan penyalah guna narkotika dari ketergantungan zat adiktif yang mencakup penerimaan awal, rehabilitasi medis, dan/ atau rehabilitasi sosial, serta pasca rehabilitasi. Dukungan faktor lingkungan yang mempengaruhi keberhasilan rehabilitasi meliputi lingkungan ekonomi, sosial, dan politik. Tujuan dari penelitian ini adalah untuk mengetahui dukungan ekonomi, sosial, dan politik dalam keberhasilan rehabilitasi penyalah guna narkotika di Klinik Badan Narkotika Nasional Wilayah Provinsi Jawa Tengah. Metode penelitian ini merupakan penelitian kualitatif dengan jenis penelitian studi kasus. Penelitian menggunakan analisis Van Horn Van Metter dengan pendekatan variabel lingkungan. Informan dalam penelitian ini meliputi 8 informan utama dan 6 informan triangulasi. Hasil penelitian menyebutkan bahwa dukungan lingkungan ekonomi, sosial, dan politik mempengaruhi keberhasilan implementasi rehabilitasi berkelanjutan. Dukungan ekonomi klien mempengaruhi kemauan klien untuk mengakses layanan rehabilitasi. Dukungan sosial yang mempengaruhi rehabilitasi dapat dari keluarga dan masyarakat. Sedangkan dukungan politik baik secara anggaran, peraturan, maupun regulasi yang memfasilitasi penyelenggaraan layanan rehabilitasi narkotika. Hasil penelitian ini dapat menjadi dasar perbaikan kebijakan serta penguatan dukungan lingkungan dari seluruh stakelholer. Kata Kunci: Kebijakan, Ekonomi, Sosial, Politik, Narkotika.